(untitled) (Cardiovascular Journal, 2015)
Background: Hypertension is a major public health problem in both the developed and developing countries and the leading cause of morbidity and mortality globally. The risk factors for hypertension, which can largely be prevented through simple health promotion and preventive measures, are mostly known. However, evidence on strategies for prevention of hypertension in Bangladesh is not available. The aim of this review study was to identify and discuss different approaches to prevent hypertension in Bangladesh. Methods: We performed a systematic search using electronic as well as manual methods for published and unpublished reports of prevention of hypertension. We then identified and discussed prevention strategies for hypertension suitable for Bangladesh context. Results: Several methods have shown to prevent hypertension. However, the challenge remains in implementing these methods in resource poor settings. Integrated action based on comprehensive policy and stepwise implementation should be adopted taking into consideration of local needs. Hypertension prevention should focus on awareness generation, health promotion and reduction of common risk factors using a combination of population based approach and targeted individual interventions. Conclusion: Consorted actions should be taken as a priority to prevent hypertension through intersectoral, multidisciplinary and multilevel approach by the Government and stakeholders for creating greater awareness and healthy life-style. DOI: http://dx.doi.org/10.3329/cardio.v7i2.22262 Cardiovasc. j. 2015; 7(2): 137-144